The Prognostic Value of CD133 in Predicting the Relapse and Recurrence Pattern of High-Grade Gliomas on MRI: A Meta-Analysis - Abdoli Shadbad, Mahdi; Hosseinkhani, Negar; Asadzadeh, Zahra; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Oncology, 2021)
Background: Cancer stem cells have been implicated in tumor relapse, tumor invasion, and cancer therapy resistance in high-grade gliomas; thus, characterizing cancer stem cell-related markers might help develop targeted therapy, predict the prognosis and response rate of affected patients. Preclinical studies have reported that CD133, as a cancer stem cell marker, is implicated in tumor recurrence and cancer therapy resistance in high-grade gliomas; however, clinical studies have reported controversial results regarding its prognosis in affected patients. Methods: We systematically searched the PubMed, Scopus, Web of Science, and Embase databases to obtain the relevant studies published before March 10, 2021, and conducted a systematic review and meta-analysis based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statements. By applying the random-effect model, the effect size of studies investigating the progression-free survival (PFS), time to local recurrence (TTL), and time to distant recurrence (TTD) were calculated using RevMan version 5.4. The heterogeneity between the included studies was studied by the I2 index and Cochran's Q test. Egger test was performed on funnel plots to investigate the potential asymmetry and publication bias among the included studies using CMA version 2. Results: Increased CD133 protein expression is associated with the inferior PFS of glioblastoma patients and patients with high-grade gliomas. Increased CD133 protein expression is also associated with increased distant tumor recurrence on MRI in glioblastoma patients and patients with high-grade gliomas and decreased local tumor recurrence on MRI in glioblastoma patients. Based on our bioinformatic study, CD133 expression in glioblastoma tissue is substantially upregulated compared to the surrounding tissues of glioblastomas and normal tissues. Besides, its upregulation is associated with a remarkable decrease in the response rate of glioblastoma patients to chemotherapy; thus, it can be a valuable marker for predicting the chemotherapy response of glioblastoma patients. Conclusion: CD133 expression is a valuable marker to predict tumor relapse and tumor recurrence patterns in high-grade gliomas patients.